Prevalence of premenstrual syndrome and premenstrual dysphoric disorder among highly trained and elite female athletes: a systematic review and meta-analysis - Granda, D.; Szmidt, M. K.; Surala, O.; Malczewska-Lenczowska, J. (Biology of Sport, 2025)
Premenstrual syndrome (PMS) involves psychological and physical symptoms affecting around 30% of reproductive-age women, while premenstrual dysphoric disorder (PMDD) is a more severe, less common form. The aim of the review was to determine whether PMS and PMDD are more common among highly trained female athletes compared to non-training women.The study protocol was registered with PROSPERO (CRD42022323111). A search of PubMed, Scopus and Web of Science (up to August 2024) identified 12 eligible studies, with 7 included in the meta-analysis. Data from 1570 female athletes and 1165 non-athletes were analysed. A total of 755 cases of PMS and 54 cases of PMDD were found in all included studies. The prevalence of PMS among athletes ranged from 8.6 to 65.8%, while the impact of symptoms on athletic performance was reported by 41.1 to 44.3% of respondents. The meta-analysis on PMS prevalence (n = 2005 women) indicated 16% lower odds for athletes compared to non-athletes, however, the result was not statistically significant (p = 0.409). The prevalence of PMDD among athletes ranged from 1.3 to 13.1%. Meta-analysis results (n = 1314 women) showed 16% higher odds ratio of PMDD prevalence among athletes compared to non-athletes, but the association was also not significant (p = 0.660). This is the first systematic review and meta-analysis on the susceptibility of women to PMS and PMDD symptoms in relation to physical activity at a professional level. The prevalence of PMS among athletes could be highly variable, while PMDD appears to be a relatively minor issue. Further research regarding PMS and PMDD in female athletes is warranted.